PENINGKATAN PERKEMBANGAN MOTORIK HALUS MELALUI TEKNIK MOZAIK PADA ANAK USIA 5-6 TAHUN - Salim, Sandora; Syukri, Muhammad; Ali, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe background of this study is children who have difficulty in fine motor skills, among others on the activity of sticking, cutting, matching. The problem in this study is: